Minat Beribadah Bagi Pertumbuhan Iman Pemuda di GKJW Kucur Kabupaten Malang - Maranatha, Yosafat; Mujianto, Yonathan (DIDAKTIKOS: Jurnal Pendidikan Agama Kristen, 2023)
The urge to perform worship is influenced by desire. Interest is the desire in a person to get what he wants without any coercion from others. The purpose of this research is to find out the characteristics, the reality of the youth's interest in worship, as well as steps to increase their interest in worship so that the faith of the youth in GKJW Kucur grows normally. This study uses a qualitative research method with a case study approach. Data collection is done by interviews, observation and documentation. Based on the results of the study it was found that the characteristics were different, as were the procedures for worship at GKJW Kucur. The characteristics of the procedures and implementation of youth worship are solemn and monotonous, stiff, causing a lack of enthusiasm. Reality shows that youth are very enthusiastic about attending services on major holidays such as Youth Christmas, Valentine's Day, and Easter. steps taken to increase youth interest in worship, namely the need for worship programs that are in accordance with the characteristics of today's youth, the importance of forming a group or community so that youth exchange ideas and encourage one another in worship, adjusting to liturgical services, materials, ecclesiastical music.